The relationship between physical activity and severity of COVID-19 symptoms in non-hospitalized individuals. (22nd July 2022) - Mitropoulos, Alexandros; Goodwill, Simon; Copeland, Robert; Klonizakis, Markos
Abstract: Background: The study explored the relationship between physical activity (PA) behaviour and severity of symptoms in people infected by coronavirus disease 2019 (COVID-19). Methods: Five hundred and thirty-three people [16% males, mean age: 45 ± 11 years, body mass index (BMI): 23.3 ± 20] took part in the study. All participants were post-COVID-19 infection. An online questionnaire was used to gather data on; participants demographics, comorbidities and treatment, symptomatology of COVID-19, quality of life (QoL) and pre- and post-COVID-19 infection PA. Results: Logistic regression revealed that only a high BMI (>25) increased the severity of (odds ratio 1.01; 95% confidence interval, 0.99–1.03) symptoms from none to mild-to-moderate. Weekly PA behaviour (min/week) did not affect the primary outcome (symptom severity) as a predictor variable and neither differ ( P > 0.05) between symptomatology for both moderate (no symptoms: 181.3 ± 202.1 vs. mild-to-moderate symptoms: 173 ± 210.3) and vigorous (no symptoms: 89.2 ± 147 vs. mild-to-moderate symptoms: 88.9 ± 148.3) PA. QoL (i.e. mobility, self-care, usual activities, pain/discomfort, anxiety/depression and perceived health) was significantly ( P < 0.05) worse post-COVID-19 infection. Conclusions: Our findings did not present an association between PA levels and mild-to-moderate COVID-19 symptoms. However, all participants exceeded the lower limit of the World Health Organization recommended, adult PA dose. This might explain the lack of PA effect, on mild-to-moderate symptoms post-COVID-19 infection. Future studies should explore the effects of PA levels in more severe cases (e.g. hospitalizations) and assess the effectiveness of PA to reduce hospitalizations, and mortality rates as a result of COVID-19 infection.